ASPEK-ASPEK KEBAHASAAAN DALAM PROSEDUR PENERJEMAHAN - Yoseph B. A. Prasaja (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. Translating a source text into a target text requires a lot of insight. The greater the translator's insight, the better the translation will be. A translator requires not only the aspects of meaning and style in the source language and the target language, and translation technique/procedure, but s/he is also required to provide detailed explanation of information presented in the text. Particularly in interpreting, an interpreter should obey the rules or principles applicable in the source and the target language. One important norm is related to the phrase structure, either the noun phrase, the adjective phrase; adverbial phrase, or other types of phrases. In reality, however, frequent violations of the phrase rules occur in that the interpreter ignores the correct translation procedures in accordance with the standard language of the target text. In this paper the author will describe the compulsion imposed by the translators, especially those that occurred in the translation classes. Beginners in the field of translation often ignore standardized translation techniques. Keywords: translation constraint; procedure; variation; factors